Aplikasi Pendukung Keputusan Tes Tipe Kecerdasan Majemuk Anak dengan Metode Simple Additive Weighting Berbasis Web - Achmad Bahtiar Efendi; Gatit Sari Chotidjah (Politeknosains, 2018)
Teachers play an important role in understanding the characteristics of their students, this is a reason for teachers to better recognize the interests and talents of their students so that interest can be directed and guided so that they can develop. Today many children have talents but do not get the support and encouragement in their schools, so many children are in fact considered learning disabled because their unique thinking patterns cannot be accommodated by schools (Susanto, 2005). This is the main problem in the Tarbiyatul Athfal Kindergarten (TK) 39 Semarang, because the teachers have difficulty in determining the interests and talents of their students because they have not been supported by the application of computerized decision support systems and methods. Therefore in this study proposed Decision Support application for multiple intelligence type tests for kindergarten-aged children using the web-based Simple Additive Weighting (SAW) method that can help facilitate the teacher in knowing the interests and talents of her students. The SAW method has the advantages of being easy to understand, more flexible, able to solve complex problems and conduct learning based on human knowledge and experience in solving problems. The SAW method or better known as the weighted sum. To answer the question, the researcher uses a Likert scale to facilitate conclusions.